OGILVIE´S SYNDROME - Rockbrand Campos, Leyla Priscilla (2021)
Ogilvie's syndrome describes an acute colonic pseudo-occlusion, whose pathophysiology is still misunderstood. This pathology consists in distension of a portion or all the colon and rectum in the absence of intrinsic or extrinsic mechanical obstruction. This pathology can evolve towards ischemia and perforation, so its clinical suspicion is of high importance. This review of the Ogilvie syndrome it's meant to be as a guide to the medical community based on the most recent evidence to diagnose and thus be able to manage this pathology, avoiding its complications. Its diagnosis must be timely and early, it is made by combining clinical manifestations and radiological studies, always ruling out other diagnostic possibilities. The initial treatment should be conservative, if the patient does not show clinical improvement, other therapeutic measures should be analyzed; such as pharmacological treatment, endoscopic decompression and finally or in case of complications the surgical intervention.